Case Studies on Marriage for Children Who Have Not Reached the Age Limit - Zefanya Angellin Chen; Vanessa Vanessa; Felicia Amanda Sulistio (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Marriage is a living union for the legalization of sexual relations and to obtain offspring or children, which is regulated by the rule of law. Article 1 of the Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage states that "Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on Belief in the One Supreme God. â€ Indonesia is rife with cases of underage child marriage, which means that they have not reached the age of 19 (nineteen) years. Cases of child marriage do not only occur in remote areas, but also occur in big cities. Law Number 16 of 2019 states that "Marriage can only be permitted if a man and a woman have reached the age of 19 (nineteen) years". This case occurred because of many factors, namely, socio-cultural factors, economic problems, low education, religion, unemployment, social media, thoughts and beliefs, and orders from parents. Young marriages have a negative effect because teenage husband and wife are not mentally and physically ready to build a family. Good and maximum handling is needed from the state, government and the surrounding environment to prevent an increase in cases of underage marriages. If treatment is given or carried out properly, it will produce positive impacts such as reducing infant and maternal mortality rates and reducing divorce rates.